Founder or Joiner? The Role of Preferences and Context in Shaping Different Entrepreneurial Interests - Roach, Michael; Sauermann, Henry (Management Science, 2015)
Entrepreneurial ventures rely not only on founders but also on “joiners”—start-up employees who are attracted to entrepreneurship, but who do not want to be founders themselves. Drawing on both preference and contextual theories of entrepreneurship, we examine how individuals’ interest in being a founder, a joiner, or neither forms prior to the first career transition. We find that although individuals with founder and joiner interests share similar preferences for entrepreneurial job attributes such as autonomy and risk, their preferences for these attributes also differ in significantly meaningful ways. Contextual factors such as norms, role models, and opportunities exhibit very different relationships with founder and joiner interests. Most interestingly, our results suggest that preferences and context interrelate in unique ways to shape different entrepreneurial interests. In particular, an interest in being a founder is most strongly associated with individuals’ preferences for entrepreneurial job attributes, whereas contextual factors do little to shape a founder interest in individuals who lack these preferences. An interest in being a joiner, on the other hand, is associated with both preferences and context, and this relationship is most pronounced for individuals with preferences that predispose them toward entrepreneurship. This study highlights joiners as a distinct type of entrepreneurial actor and demonstrates the importance of considering the interplay between preferences and context in the study of entrepreneurship. This paper was accepted by David Hsu, entrepreneurship and innovation.